MAXIMIZING JOINT ATTENTION IN CHILDREN WITH AUTISM SPECTRUM DISORDER: THE IMPACT OF CHILD-CENTERED PLAY THERAPY AT SD MUHAMMADIYAH 1 CANDI LABSCHOOL UMSIDA - Savitri, Oky Tania; Ansyah, Eko Hardi (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to examine the effectiveness of Child-Centered Play Therapy (CCPT) in enhancing joint attention skills in children diagnosed with Autism Spectrum Disorder (ASD), a critical component of social interaction and communication often underdeveloped in this population. Method: Utilizing a Single-Case Experimental Design (A-B-A), the research focused on a 7-year-old child with ASD enrolled at SD Muhammadiyah 1 Candi Labschool UMSIDA. The intervention was conducted over two sessions across two weeks, with joint attention skills evaluated pre- and post-intervention. Results: The findings demonstrate a significant improvement in the child's Responding to Joint Attention (RJA), particularly in following visual cues and shared object referencing. However, Initiating Joint Attention (IJA), such as initiating pointing or object sharing, showed minimal improvement, indicating the need for extended or supplementary interventions. Novelty: This study contributes to the limited empirical evidence on the application of CCPT for joint attention development in ASD populations within Indonesian elementary school settings, offering insights for early intervention strategies. Further research involving a larger sample and longer implementation period is recommended to validate and generalize the findings.